2004
DOI: 10.1200/jco.2004.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan Compared With No Therapy After Response to Surgery and Carboplatin/Paclitaxel in Patients With Ovarian Cancer: Multicenter Italian Trials in Ovarian Cancer (MITO-1) Randomized Study

Abstract: The present analysis indicates that consolidation with topotecan does not improve PFS for patients with advanced ovarian cancer who respond to initial chemotherapy with carboplatin and paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(58 citation statements)
references
References 25 publications
4
54
0
Order By: Relevance
“…We also documented a manageable toxicity profile for docetaxel -irinotecan that reduces neurotoxicity compared to using a higher dose of docetaxel alone although at the expense of increased diarrhoea. However, the recent results of two randomised phase III studies (De Placido et al, 2004;Pfisterer et al, 2005) have failed to demonstrate an improvement in survival with the addition of four cycles of the topoisomerase-I inhibitor topotecan after standard carboplatinpaclitaxel as first-line treatment for EOC. Although the MITO-1 study (De Placido et al, 2004) can be criticised for only effectively assessing the concept of consolidation therapy, as 87% of patients randomised to topotecan or placebo had already obtained a complete response to standard treatment, patients were randomised at registration in the GINECO/AGO-OVAR trial (Pfisterer et al, 2005) and 78% of those randomised to sequential topotecan received this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We also documented a manageable toxicity profile for docetaxel -irinotecan that reduces neurotoxicity compared to using a higher dose of docetaxel alone although at the expense of increased diarrhoea. However, the recent results of two randomised phase III studies (De Placido et al, 2004;Pfisterer et al, 2005) have failed to demonstrate an improvement in survival with the addition of four cycles of the topoisomerase-I inhibitor topotecan after standard carboplatinpaclitaxel as first-line treatment for EOC. Although the MITO-1 study (De Placido et al, 2004) can be criticised for only effectively assessing the concept of consolidation therapy, as 87% of patients randomised to topotecan or placebo had already obtained a complete response to standard treatment, patients were randomised at registration in the GINECO/AGO-OVAR trial (Pfisterer et al, 2005) and 78% of those randomised to sequential topotecan received this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its favored toxicity profile, the doublet therapy therefore remained the standard of care 13 . In a separate phase iii study examining the utility of topotecan consolidation therapy after standard chemotherapy, findings showed that pfs and os were not significantly affected by that addition, and the trial was concluded to be negative 14 . Interestingly, a recent investigation by Katsumata et al, which compared the efficacy of a dose-dense combination of paclitaxel and carboplatin with the standard combination regimen, showed correlating evidence in the form of a pfs and an os favouring the dose-dense regimen 15 .…”
Section: Pfs and Os In The Setting Of First-line Treatment Of Ovarianmentioning
confidence: 99%
“…Four trials underestimated the actual outcome (A/E ratio of >1.25), Eleven trials were accurate (A/E ratio of 0.75‐1.25), and 5 trials overestimated the outcome (A/E ratio of 0.75) (Table 2). 12, 14, 17, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46 The A/E ratios ranged from 0.5 to 1.6, with a mean and median ratio of 1.0 and 1.0, respectively (Fig. 3).…”
Section: Resultsmentioning
confidence: 98%
“…A total of 3 and 7 studies were excluded from the OS15, 23, 29 and PFS17, 36, 38, 42, 43, 44, 45 analyses, respectively. This confirmed a statistically significant difference ( P = .001).…”
Section: Resultsmentioning
confidence: 99%